Early-career experiences of TR practitioners in Australia, the United States, and Canada - Gulamhusein, Shemine; Alford, Stewart; Hooker, Taylor (My University, 2021)
The objective of this article is to draw attention to the negotiations and navigations of early-career practitioners within the discipline of therapeutic recreation (TR). Three of us, from Australia, Canada, and the United States, who are actively engaged in practice and scholarship, come together to discuss the challenges we each face to highlight the importance of local and global collaborations, and to critically account for the complexities of entering the TR field. Ultimately, this article aims to explore why a practitioner would commit to the profession of TR, and obtain and maintain a TR certification.
Keywords: work experiences; recreational therapy; allied health personnel